ON USE OF FACTOR ANALYSIS IN ANALIZING SERVICE QUALITY PERFORMANCE - Gandhi Pawitan (Indonesian Management and Accounting Research, 2007)
Performance measurement within organization is not only in financial aspect but also in a quality of services must take into account. This measure becomes extremely important when organization focus in purely delivering services, such as in higher education institution. This paper has an objective to identify key factors which affect services quality performance of the operational of the higher education organization. A SERVQU AL approach provides a description of the service quality, and factor analysis guides a clear overview of an important factor of the service quality performance. The approach was applied to measure performance of the service quality within the Faculty of Social and Political Science, Parahyangan Catholic University. The result indicated a service quality performance measurement gives guidance in service quality control and improvement.JELCiassification: QOKeywords: SERVQUAL. performance measurement, quality improvement.